U.S. Marine Corps aviation since 1912 - Mersky, Peter B. 1945- (Naval Institute Press, 2009)
This heavily illustrated work is the only book to describe the entire history of the U.S. Marine Corps air arm. With hundreds of rare photographs, this fourth edition represents a major redesign and update of the last edition, published more than a decade ago. Chapters include descriptions of early development and training, as well as combat deployments during World War I and in Central America. World War II and Korea, Vietnam, the Balkans, and Southwest Asia campaigns are also well covered. The book s emphasis is on the Marines who made up the air squadrons, developed the aircraft and tactics, and fought the battles as the main support of troops on the ground. The text includes first-person accounts and comments from many participants aviators and crewmen alike